TEACHING STRATEGIES IN UNDERGRADUATION IN NURSING:A DESCRIPTIVE STUDY - Aida Maris Peres; Jessika Rodrigues Rocha; Cristiano Caveião; Ana Carla Lemos Hipolito; Maria de Fátima Mantovani (Universidade Federal do Paraná, 2018)
Objective:To identify teaching strategies that facilitate nurses' training according to the views of nursing studentsMethod: A quantitative, descriptive and cross-sectional study carried out in three universities in the south of Brazil, through a semi-structured questionnaire, with 258 nursing students, in March and April, 2014. Data were analyzed by descriptive statistics using absolute and relative frequencies. Results:Regarding teaching strategies, it was found that the audiovisual resources: 67 (33.16%), dynamic classes: 67 (33.16%), discussion of scientific articles: 60 (29.70%), group work 47 (23.26%) were the strategies that facilitate learning during lecture classes. Less cited teaching strategies included seminars, summaries (students are asked to summarize what they learned in previous classes) and discussion of scientific articles and case studies. On facilitating strategies, 48 (20%) students sought other learning opportunities in addition to those offered in the undergraduate program.Conclusions:It is concluded that the nursing students perceive many facilitating methods as teaching strategies. The strategies most often reported were dynamic classes, group work and problematization.